Pumping phase modulation analysis for operational quality of a pumped-storage generating system. (1st November 2019) - Li, Huanhuan; Xu, Beibei; Mahmud, Md. Apel; Chen, Diyi; Zhang, Jingjing
Highlights: Pumping phase modulation model fills obvious gaps in the theoretical modeling. Coordinated characteristic and reactive power flow in multiple units are revealed. Transition mechanism in late/leading phase modes reduces the power generation loss. Phase modulation study benefits the integration of PSGS with multi-energy sources. Abstract: The integration of pumped-storage power with multi-energy sources pushes the electricity generation to concern about the voltage stability and reactive power balance. This study focuses on the effect of pumping phase modulation on the operational quality of the pumped-storage generating system. A precise mathematical model of the pumped-storage generating system with multiple units is presented, aiming at the analysis of dynamic performance and stability under the operating mode of the pumping phase modulation at timescale of seconds. The result reveals that the favorable capacity of leading phase modulation for unit 1 significantly decreases the release of reactive power of unit 2 owing to the effect of reactive power flow in different units. It is also obtained that the different amplitudes of external step disturbances cause the operation transition between the late phase and leading phase, while the random disturbances result in a fuzzy phase domain that refers to the obscure boundary of the leading & late phase modulation conditions in time domain (6.88 s, 10 s). The large disturbance decreases the leading phase depth of unit 1, which indirectly reduces the surplus reactive power absorbing of unit 2. The implemented method and results obtained from this method are beneficial to the risk mitigation and vibration diminishment of pumped-storage generating systems, which contributes to maximize the asset efficiency of pumped-storage power stations for generating electricity in multi-energy integration setups.